Navigating Role Conflict and Emotional Strain: A Qualitative Study on the Psycho-Social Challenges of Special Educators in Inclusive Education - Ms. Smriti Maini,; Dr Aanchal Chaudhary, (The Bioscan, 2025)
Special educators working in inclusive education settings face significant psycho-social challenges, particularly in managing role conflict and emotional strain. Balancing responsibilities such as teaching, advocacy, and providing emotional support to students with disabilities often leads to role ambiguity and stress (Forlin, 2019). Through semi-structured interviews and participant observation, this research explores how these challenges impact educators’ emotional well-being and professional satisfaction. Findings reveal that role conflict and emotional exhaustion are prevalent, with educators frequently overwhelmed by the competing demands of their roles (Hughes et al., 2021). Coping strategies, including peer support, self-care, and professional development, were identified as vital in managing stress and maintaining well-being (Miller et al., 2020). This study highlights the need for greater institutional support to address these challenges, emphasizing the importance of policies that promote emotional resilience and professional satisfaction among special educators, ultimately enhancing the effectiveness of inclusive education (Lindsay, 2020).